The Effort of TheHead of Madrasah in Procurement of Education Facilities in MA Nurul Huda - Fajar, Deni Malik (IAIN Syekh Nurjati Cirebon, 2021)
This research aims to find out how the state of educational facilities in MA Nurul Huda Munjul Cirebon Regency, how the efforts of madrasah heads in the procurement of educational facilities in MA Nurul Huda Munjul Cirebon Regency, and the results of madrasah school efforts in the procurement of educational facilities in MA Nurul Huda Munjul Cirebon Regency. This type of research is qualitative. In this study in collecting data using observation methods, interviews and documentation. The sources on the study were the head of the madrassa, the deputy head of the madrassa in the field of facilities and infrastructure, a teacher and a student. The results of this study show that the state of educational facilities in MA Nurul Huda Munjul Cirebon Regency is in good condition, but there are some that have not been maximized. The efforts of the head of madrasah in the procurement of educational facilities in MA Nurul Huda Munjul Cirebon Regency have also been good but there are some who are still in planning and are waiting for funds. The results of the efforts of madrasah heads in the procurement of educational facilities have also met significant results. It is recommended the need for procurement for facilities that have not been maximized.Key words: Head of madrasah, procurement and educational facilities.Â Penelitian ini bertujuan untuk mengetahui bagaimana keadaan sarana pendidikan di MA Nurul Huda Munjul Kabupaten Cirebon, bagaimana upaya kepala madrasah dalam pengadaan sarana pendidikan di MA Nurul Huda Munjul Kabupaten Cirebon, dan hasil dari upaya madrasah sekolah dalam pengadaan sarana pendidikan di MA Nurul Huda Munjul Kabupaten Cirebon. Jenis penelitian ini adalah kualitatif. Pada penelitian ini dalam mengumpulkan data menggunakan metode observasi, wawancara dan dokumentasi. Narasumber pada penelitian ini adalah kepala madrasah, wakil kepala madrasah bidang sarana dan prasarana, seorang guru dan seorang murid. Hasil dari penelitian ini menunjukkan bahwa keadaan sarana pendidikan di MA Nurul Huda Munjul Kabupaten Cirebon dalam keadaan baik, namun ada beberapa yang belum maksimal. Upaya kepala madrasah dalam pengadaan sarana pendidikan di MA Nurul Huda Munjul Kabupaten Cirebon juga sudah baik namun ada beberapa yang masih dalam perencanaan dan sedang menunggu dana. Hasil dari upaya kepala madrasah dalam pengadaan sarana pendidikan juga sudah menemui hasil yang cukup signifikan. Disarankan perlunya pengadaan bagi sarana yang belum maksimal.Kata kunci: Kepala madrasah, pengadaan dan sarana pendidikan.